XRD study of iron oxide nano powders prepared using aloevera extract - D. B. Roy, T.K. Mandal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Iron oxide nanopowders (IONPs), Fe2O3,are synthesized by using Aloe-Vera leaf extract via green synthesis method. The nanopowder of IONPs prepared through this environment friendly method is found to be very effective in various applications such as electrical and optical sensors, MRI, memory devices, photocatalysis etc. The as prepared nanopowders were characterized using X-ray diffraction (XRD) for crystallite size and crystal symmetry. The hexagonal shape with the R3C space group is confirmed by XRD study, for for as preparedFe2O3 nanopowders. The average crystallite size of the as synthesized Fe2O3 nanopowders, as calculated from XRD, is 30 nm.